PCK Based Learning Design: Development Through Design Research to Improve Matematics Teachers’ Teaching Skills - Veni Rahayu, Diar; Muhtadi, Dedi (Department of Mathematics Education Program IPI Garut, 2025)
Untuk dapat mengajar secara efektif, seorang guru tidak hanya dituntut memahami konten materi, tetapi juga mampu menyampaikannya sesuai dengan karakteristik siswa melalui penguasaan Pedagogical Content Knowledge (PCK). Keterampilan ini menjadi kunci pencapaian tujuan pembelajaran. Penelitian ini bertujuan mengembangkan desain pembelajaran berbasis PCK yang dapat meningkatkan keterampilan mengajar guru matematika. Metode yang digunakan adalah design research model Plomp, yang terdiri dari tahapan preliminary research, prototyping phase, dan assessment phase. Subjek penelitian adalah tiga guru matematika, dengan instrumen berupa RPP dan lembar observasi. Hasil penelitian menunjukkan bahwa: (1) Desain pembelajaran berbasis PCK dapat dikembangkan dalam bentuk RPP yang mengacu pada konsep PCK John K. Lannin, dengan adaptasi berupa penekann pada identifikasi student thinking, pemilihan representasi matemais yang bervariasi, serta perencanaan antisipasi kesulitan siswa berdasarkan PCK Mathematics Lesson Plan Template; dan (2) RPP tersebut terbukti efektif dalam meningkatkan keterampilan mengajar guru. Secara keseluruhan, desain pembelajaran berbasis PCK mampu memfasilitasi pengembangan keterampilan praktis mengajar secara nyata, serta meningkatkan kemampuan esensial dalam pembelajaran matematika yang bermakna. Implikasi dari penelitian ini aalah bahwa adaptasi model PCK Lannin dapat dijadikan acuan dalam penyusunan perangkat pembelajaran yang lebih kontekstual, sehingga guru lebih siap menghdapi keragaman cara berpikir siswa di kelas. To be able to teach effectively, a teacher is not only required to understand the content of the material, but also to be able to convey it according to the characteristics of the students through mastery of Pedagogical Content Knowledge (PCK). This skill is the key to achieving learning objectives. This study aims to develop a PCK-based learning design that can improve the teaching skills of mathematics teachers. The method used is the Plomp design research model, which consists of the stages of preliminary research, prototyping phase, and assessment phase. The subjects of the study were three mathematics teachers, with instruments in the form of lesson plans and observation sheets. The results of the study indicate that: (1) PCK-based learning designs can be developed in the form of lesson plans that refer to John K. Lannin's PCK concept, with adaptations in the form of emphasis on identifying student thinking, selecting varied mathematical representations, and planning to anticipate student difficulties based on the PCK Mathematics Lesson Plan Template; and (2) the lesson plans have proven effective in improving teachers' teaching skills. Overall, PCK-based learning design is able to facilitate the development of practical teaching skills in real terms, as well as improve essential abilities in meaningful mathematics learning. The implication of this research is that the adaptation of Lannin's PCK model can be used as a reference in compiling more contextual learning tools, so that teachers are better prepared to deal with the diversity of students' ways of thinking in the classroom.